PERILAKU HIDUP BERSIH DAN SEHAT SEBAGAI METODE PENCEGAHAN ANEMIA REMAJA - Ani Ani; Astri Yuliandini; Suhartini Suhartini (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The incidence of anemia has the highest cases or prevalence (60%) in Southeast Asian countries, especially in school-age children, the prevalence of anemia in Indonesia at the age of 15–24 years is quite high at 32%. Anemia in adolescence can be prevented by providing knowledge to increase understanding through counseling activities related to the implementation of clean and healthy living behaviors (PHBS). This activity aims to increase the understanding of adolescents related to anemia. This activity is one of the educational actions that adopt the Clean and Healthy Behavior (PHBS) method, using the Focus Group Discussion (FGD) model, with discussion and question and answer techniques. This activity has added to the understanding and insight of teenagers regarding anemia, especially how to prevent it, and has been welcomed enthusiastically by teenagers, This is because the material presented is of interest to teenagers